Preparedness to manage volcanic and seismic risk: a study of risk perception in the Azores - Arroz, Ana Margarida Moura (2010)
This work focuses on the last phase of a research project on volcanic and seismic risk perception (TOPOI METUS. Social cosmographies of danger. Risk perception of natural hazards) that has been carried out in the archipelago of the Azores during the last three years. It presents findings on perceived risk dimensions (i.e. risk characterization; risk profile evaluation; systems’ vulnerability evaluation; risk management before, during and after the crisis; and trust in processes and entities responsible for risk management and information processes), based on data obtained through the application of an instrument (survey questionnaire) specifically created to address volcanic and seismic risk issues in the archipelago. It also represents an attempt to achieve a more precise understanding of communication and actions thought to be taken before a crisis, and during the response and recovery phases of a disaster, as well as the trust involved in those situations, by comparing results with findings obtained earlier through in-depth interviews conducted at a previous stage of the research.